Religious competence in social work practice: The UK picture - Panagiotis Pentaris (Social Work and Society, 2013)
Social work principles include cultural competence and cultural awareness as major matters for effective social work practice. Religion is one of the strands for non-discriminatory practice. However religious competence has not been referred as such. This essay seeks to comment on an observed need in the UK for further development and implementations of social work principles and practice. The religious diversity in the UK shows demand for multi-faith and multi-religious education, knowledge and awareness, which will promote effective social work practice.